Untangling the making and governing of Hong Kong teachers through neoliberal, Confucian, and affective technologies: with and beyond Foucault. Issue 2 (15th March 2023) - Lin, Min; Zhao, Weili
ABSTRACT: This paper investigates the making and governing of Hong Kong teachers along and beyond a Foucauldian governmentality lens, untangling how the three technologies along neoliberalism, Confucian thesis, and affective dimensions play with and against one another in conducting the conduct of teachers. Through a discourse analysis of 27 local teachers' interview texts, we find Hong Kong teachers are both morally divided and redeemed as an effect of the entangled governing dynamics. First, the neoliberalized technologies of performativity and accountability are turning teachers into "service providers" accountable for incessant evaluations from the institutions, students, and parents. Second, such neoliberal rationalities collide with a Confucian respect for teachers to the extent that teachers feel not-respected, sad, and disappointed. Last, some teachers, amidst such contested situations, turn to affective support, i.e., a family-like teacher-student relationship, that ends up redeeming them from a negative governing grid towards maintaining a congruent self-identification. With this finding, this paper further explicates Confucian affective teacher-student relationship as a foundational historical-cultural episteme that largely conditions today's teaching and learning in Confucian context. This recognition enables us to re-ponder the theoretical-methodological-epistemological complexities in applying Foucault's framework to an Asian context along a (de/anti/post)-colonial gesture.